Clinical and safety outcomes of laparoscopic nephrectomy with renal autotransplantation for the loin pain‐hematuria syndrome: a 14‐year longitudinal cohort study. Issue 2 (May 2016) - Zubair, Adeel S; Cheungpasitporn, Wisit; Erickson, Stephen B; Prieto, Mikel
Abstract: Objective: The objective of this study is to assess clinical and safety outcomes after laparoscopic nephrectomy with autotransplantation for loin pain‐hematuria syndrome (LPHS). Methods: We conducted telephone interviews using structured questionnaires and retrospectively reviewed data on all patients who underwent laparoscopic nephrectomy with autotransplantation for LPHS between January 2000 and May 2014. Results: A total of 24 laparoscopic nephrectomies with renal autotransplantation of 21 patients with LPHS were reviewed. Eighty‐three per cent were female with a mean age of 31 years. Postoperatively, graft loss resulting in subsequent nephrectomy occurred in two patients; However, no patients died (median follow‐up = 22 months, range 5 to 78 months) or required dialysis (median follow‐up = 10 months, range 0.2 to 178 months). There was no significant difference in estimated glomerular filtration rate (eGFR) before and after surgery (100 ± 22 vs. 97 ± 23 mL/min/1.73 m 2 ; P = 0.37). Among 14 patients (16 autotransplantation) with telephone follow‐up, 14 (88%) resulted in pain relief and no operation resulted in worsening pain. All procedures resulted in immediate pain relief; pain recurrence was reported after two procedures. However, those patients had pain‐free period up to 36 months. The quality of life was better after 15 (94%) autotransplantation with higher employment rate (44% vs. 69%; P = 0.04). Two patients with graft loss reported better pain control and quality of life. Conclusions: Renal autotransplantation is a possible treatment option for LPHS refractory to conservative medical treatment. It can offer pain relief and better quality of life. Despite postoperative risk, it seems to be safe for survival and renal outcomes.